2020
DOI: 10.1186/s43055-020-00164-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of brain structural magnetic resonance imaging in the assessment of hippocampal subfields in Alzheimer’s disease

Abstract: Background Volumetric MR neuroimaging can visualize the pattern of hippocampal subfield atrophic changes in AD. This can be used as a biomarker in early diagnosis of AD and allow early treatment to improve memory, behavioral symptoms, and delay the cognitive deterioration. The aim of this work is to assess the role of the volumetric study of different hippocampal subfields as a post-processing technique of structural MR imaging in patients with Alzheimer’s disease of different severity of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Secondly, it may be that in the whole‐brain MRI data currently used, the brain parts related to personality are not shown or not obvious enough. We also find some related references like [27], which conducted experiments about the relationship between Alzheimer disease and hippocampus. The results show some significant evidence of correlation, which gives us a hint that some information may be hidden in specific areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Secondly, it may be that in the whole‐brain MRI data currently used, the brain parts related to personality are not shown or not obvious enough. We also find some related references like [27], which conducted experiments about the relationship between Alzheimer disease and hippocampus. The results show some significant evidence of correlation, which gives us a hint that some information may be hidden in specific areas.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In imaging, hippocampus volumetry is the most well-established structural biomarker for AD, especially for early diagnosis [ 27 ]. Studies have also shown volumetric analysis by high-resolution T1 images increases the sensitivity and specificity of diagnosis [ 28 ]. Furthermore, as it does not use ionizing radiation, MRI is considered safe and non-invasive.…”
Section: Reviewmentioning
confidence: 99%